The phase boundaries of the H-Er, H-Sc and H-Yb systems at 295K deduced from changes of film resistance - Surplice, N.A.; Kandasamy, K. (My University, 1982)
The phase boundaries of the H-Er, H-Sc and H-Yb systems were found by measuring changes of resistance as a function of atomic ratio r (r=H/Me) while films of the metals were hydrided at 295K. For H-Er the solution phase was between r=0 and 0.23 and the single-phase dihydride region was from r=1.9 to 2.1. For H-Sc the solution phase ended at r=0.17 and the single-phase dihydride began at r=1.1, while for H-Yb the solution phase ended at about r approximately=0.15. The dissociation pressure of ScH2 was about 5*10-2 Torr at 295K.